PENEGAKAN HUKUM PIDANA TERHADAP KONFLIK ANTAR RAS PADA PERISTIWA DISKRIMINASI RASISME MAHASISWA PAPUA DI SURABAYA TAHUN 2019 - Topik Hidayat,; Tiara Putri Hendriani, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
The incident of racial discrimination against Papuan students in Surabaya in 2019 was one of the cases that caused inter-ethnic conflict and triggered protests in various regions of Papua. This incident started from the allegation of vandalism of the red and white flag by Papuan students who were then surrounded and insulted by a number of officers and mass organizations. This incident provoked a strong reaction from the Papuan people who felt that their rights as Indonesian citizens were violated. This incident also showed the weakness of criminal law enforcement against the perpetrators of racial discrimination who were only given light sentences, while the protesters who demanded justice received heavy sentences. This incident threatened the unity and integrity of the Indonesian nation based on Pancasila and the 1945 Constitution. Therefore, there is a need for a firm and fair legal effort against the perpetrators of racial discrimination, as well as a constructive dialogue and inclusive reconciliation between the government and the Papuan people to resolve this problem peacefully and with dignity